Cervical spinal schwannoma with rapid onset quadriplegia mimicking acute subarachnoid hemorrhage - Neel P. Mistry, MD; Kyle M. Moulton, MD; Viktor A. Zherebitskiy, MD; Lissa M. Peeling, MD; Roland N. Auer, MD, PhD (Radiology Case Reports)
A previously healthy 56-year-old man presented with a 1-week history of progressive weakness, neck pain, and paresthesia, rapidly progressing over 24 hours to complete quadriplegia and saddle anesthesia, in keeping with an ASIA A spinal cord injury. Imaging revealed multifocal subarachnoid hemorrhage and a retro-clival lesion in the spinal canal, causing cord compression. Emergent decompressive surgery was performed. Intra-operative pathology revealed a high cervical subarachnoid hemorrhage and a spindle cell tumor, later confirmed to be a schwannoma with ruptured sclerotic vessels. Histopathologically, the tumor displayed classic features of Antoni A and Antoni B tissue types, along with S-100 positivity and low Ki-67 index. Schwannomas, when they bleed, can pose clinical and diagnostic imaging challenges due to hemorrhage obscuring the tumor, and overlapping radiological features with other spinal neoplasms. Timely recognition and multidisciplinary management are crucial for a favorable outcome. This case highlights that benign schwannomas can cause hemorrhage, rapid evacuation of which allows the usually benign clinical course and prognosis of schwannomas to supervene.